FEMINISME DALAM PERGELARAN WAYANG KULIT PURWA TOKOH DEWI SHINTA, DEWI KUNTI, DEWI SRIKANDI - Ariani, Iva (Jurnal Filsafat "WISDOM", 2016)
This research is a qualitative research which aims to understand the real position of woman in Javanesse culture based on the story of shadow puppets (wayang kulit purwa) performance and to know the values of feminism which relevant with the a woman's life in Java. The results of this study indicate that shadow puppet purwa is a phenomenal piece of art that have stories that can be used as a metaphor for human life. The values of feminism taught in shadow puppet which is that women in puppets depicted in figure Dewi Shinta, Srikandi and Kunti are the attitude of devotion and respect for her husband both in joy and sorrow, loyal and obedient to her husband though it should be a co-wife, always maintain purity, religious, and skilled defending her husband in trouble. Those values are widely used as the teaching of women's lives in Java that uphold the values of loyalty towards her husband and patience and sincerity live and life.